Isolation, Purification and Characterisation of Papaya Pectinesterase - Ashraf, Fayyaz (1993)
Pectinesterase (EC.3.1.1.11) is a pectic enzyme that can have a great impact in the fruit and vegetable processing technology because of its potential effect on the quality of the finished products. This project was designed to extract, purify and study the properties of the pectines terase found in the papaya (Carica papaya L. var. Exotica) fruit. Studies carried out showed that the incubation time, pH and NaCI concentration influenced the extraction of the enzyme from the papaya fruit. A maximum activity of 7.0 µmole of carboxyl groups/minlml (7.0 units/ml) was obtained when 2MNaCI solution (pH 8) and an incubation time of five hours were used. The procedure adopted for purification resulted in a 250-fold purification (784 units/mg protein) with a 45% recovery of the enzyme activity. The enzyme preparation was confirmed to be homogeneous by gelfiltration and non-denaturing polyacrylamide gel electrophoresis and it has an apparent molecular weight of approximately 32,000 Daltons. The purified enzyme was further characterised as a function of NaCI concentration, pH and temperature. Its kinetic properties were also studied. The activity was found to be linear up to 20 minutes with an enzyme concentration of up to 6.42 µg protein. Maximum activity was obtained using 0.25M NaCl solution, pH 8.0 and 65 °C. The energy of activation of the enzyme was calculated to be 5690 c al mot-i. A Q10 of 1.29 was obtained for the temperature range of 30-50°C at pH 7.0. The K value of m the enzyme for citrus pectin as a substrate was 0.1125 mg/ml, corresponding to a V max value of 730 µmole/min/mg proteiri.The Turnover number was calculated as 23360 mole/(mole. min). Inhibition studies showed that polygalacturonic acid acted as a competitive inhibitor. On the other hand, alginicac id exhibited a competitive-non-competitive type of inhibition while sucrose displayed an uncompetitive type of inhibition. The D values (time to inactivate 90% of the enzyme) at 55, 60, 65 and 70°C at pH 4.0 were estimated to be 112.14, 23.78, 8.33 and 1.71 minutes, respectively. Lower inactivation rates were observed for pH 7.5, with the D values ranging from 143.27 to 1.67 minutes for temperatures between 60 to 75°C.